Chromatin inspired bio-condensation between biomass DNA and guanosine monophosphate produces all-nucleic hydrogel as a hydrotropic drug carrier - Suryakamal Sarma; Neha Thakur; Nidhi Varshney; Hem Chandra Jha; Tridib K. Sarma (Communications Chemistry)
Abstract The integration of biomolecules into supramolecular nanostructures forms the basis of the natural world. Naturally occurring liquid-liquid phase separation resulting in biomolecular condensates has inspired the formation of biomolecule-based smart materials with multi-dimensional applications. A non-covalent bio-condensation between biomass DNA and guanosine monophosphate (GMP) has been described, mimicking chromatin folding and creating a unique “all-nucleic” DNA-GMP condensates. These condensates initiate the formation of G-quadruplex-based superstructures, assembling into super-helical fibres driven by synergistic hydrogen bonding and stacking, which have been thoroughly investigated. This simple, one-step method for the bio-condensation of biomass DNA leads to an “all-nucleic” hydrogel with higher-order self-assembly and excellent mechanical properties. While most of the reported DNA based biomaterials, including hydrogels, require precisely sequenced and molecularly architectured DNA building blocks, we have developed a simple, universal, and facile bio-condensation method that utilizes biomass DNA acquired from any bio-resource to fabricate DNA hydrogels. The hydrogel efficiently encapsulates and sustains the release of both hydrophilic and hydrophobic drugs, demonstrating its competency as a drug carrier. We believe this energy-efficient and low-cost method represents a new technique for using biomass DNA as building blocks for the next generation of soft materials.